(3eaJGM GdWHs - (3Ydj Hf GdMSjf Hf eMeO Hf gfOh, CHh GdaQL,J (B420 (3g` s ((3eMeO Hf bWHi GdWHjH s)
(3ChdgG (B:s
(3bGd GdCSJGP CHh GdaQL Hf gfOh JUaM ENhGffG ef GdeJYdejf ebGdJi GdehSheI HGdeTQaI ai GdeONd Edi Yde GdadSaI aThbJge SghdI GdeCNP ajgG s
(3BNQgG (B:s
(3CjgG GdENhGf gPg NGJeI cJGH GdeaJGM bO hajfG VefGg ai UOQg hHd ChajfG Ydjg MJi NQL Yf MLe GdebGdI GdeTQaI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B403 - (3U(B440s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B82s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B239 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B271 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs